ANALYSIS OF THE EFFECTIVENESS OF THE RISK MANAGEMENT APPROACH IN REDUCING FINANCIAL RISK - Suharini Suharini; Ratih Hastasari (Jurnal Scientia, 2023)
The development of the banking sector in Indonesia, which is increasingly dynamic and complex, creates challenges in managing financial risk for banks such as Bank Mega. Failure to identify, measure and manage financial risks can have major consequences. Risk management is the key to overcoming financial risks, involving identifying, measuring, controlling and reporting risks. This research focuses on analyzing financial risk management at Bank Mega and aims to analyze the risk management framework, evaluate the effectiveness of the risk management approach, and provide recommendations. The data used is secondary data and literature. The results show that Bank Mega has implemented good risk management with positive performance indicators. However, it is necessary to pay attention to liquidity, asset quality and risk mitigation to increase the effectiveness of risk management. This research is expected to contribute to understanding financial risk management in the Indonesian banking sector